Evaluating the relationship between the proportion of X-chromosome deletions and clinical manifestations in children with turner syndrome - Wang, Gaowei; Liu, Xiaojing; Wang, Meiye; Wang, Jin; Zhang, Zhenhua; Allegaert, Karel; Mei, Daoqi; Zhang, Yaodong; Luo, Shuying; Fang, Yang; Li, Dongxiao; Chen, Yongxing; et al. (Frontiers in Endocrinology, 2024)
Purpose Analyze the relationship between changes in the proportion of X-chromosome deletions and clinical manifestations in children with Turner syndrome (TS). Methods X-chromosome number abnormalities in 8,635 children with growth retardation were identified using fluorescence in situ hybridization (FISH). Meanwhile, the relationship between the proportion of X-chromosome deletions and the clinical manifestations of TS, such as face and body phenotype, cardiovascular, renal, and other comorbidities in children with TS was analyzed. Results A total of 389 children had X-chromosome number abnormalities, with an average age at diagnosis of 9.2 years. There was a significant increase in diagnoses around the ages of 3 and 7 years and highest number of diagnoses at 10 years of age. 130 with XO (complete loss of an X-chromosome), 205 with XO/XX, 8 with XO/XXX, 23 with XO/XX/XXX, 19 with XO/XY, and 4 with XO/XY/XYY. Body and facial phenotypes increased with higher mosaicism proportions, with a relatively high correlation shown with Pearson correlation analysis (r = 0.26, p = 1.7e-06). The incidence of congenital heart malformations was 25.56%, mainly involving a bicuspid aortic valve, and were more common in patients who had complete loss of an X-chromosome. However, this relationship was not present for renal disease (p = 0.26), central nervous system, thyroid, or liver disease. Conclusion The mosaicism (XO/XX) is the most common karyotype of TS in screened cases. The phenotypes in children with TS may increase with the proportion of X-chromosome deletions, but the renal disease and comorbidities did not show the same characteristics.